Makna Perilaku Seksual pada Anak Usia Dini - Wulandari, Fitria; Pertiwi, Eky Prasetya; Ali, A Zulkarnain (LPPM Institut Pendidikan Nusantara Global, 2025)
Sexual education is essential in the field of education, but there are a number of limitations that must be understood by young children regarding sexual knowledge. These limitations include teaching them about the differences between the male and female human bodies and their functions, teaching them about the proper care of their bodies, including which body parts should be covered, which should not be touched by others, how to protect themselves from sexual predators, and teaching them about the two genders and their language rules, such as the penis and vagina, without substituting them with ambiguous language. in the restroom. Nevertheless, in practice, there are young children in Kindergarten X who act in ways that are inappropriate for their age in terms of sex understanding, such as adult sexual conduct. Students with the initials R, Af, and D were the samples used in this investigation. This study's overall goal is to generate knowledge and understand the meaning of sexual activity in early childhood. It also seeks to inform readers so that new learning methodologies pertaining to early sex education can be implemented in the future. The research methodology is a qualitative case study approach that uses narrative presentation to convey primary and secondary data from interviews with direct observation interview types. The results of this study shed light on what early sexual behavior means.